Determining the Origin of Tidal Oscillations in the Ionospheric Transition Region With EISCAT Radar and Global Simulation Data - Günzkofer, Florian Ludwig; Pokhotelov, Dimitry; Stober, Gunter; Liu, Huixin; Liu, Hanli; Mitchell, Nicholas; Tjulin, Anders; Borries, Claudia (Journal of Geophysical Research: Space Physics, 2022)
At high-latitudes, diurnal and semidiurnal variations of temperature and neutral wind velocity can originate both in the lower atmosphere (UV or infrared absorption) and in the thermosphere-ionosphere (ion convection, EUV absorption). Determining the relative impact of different forcing mechanisms gives insight to the vertical coupling in the ionosphere. We analyze measurements from the incoherent scatter radar (ISR) facility operated by the EISCAT Scientific Association. They are complemented by meteor radar data and compared to global circulation models. The amplitudes and phases of tidal oscillations are determined by an adaptive spectral filter (ASF). Measurements indicate the existence of strong semidiurnal oscillations in a two-band structure at altitudes <110 and >130 km, respectively. Analysis of several model runs with different input settings suggest the upper band to be forced in situ while the lower band corresponds to upward-propagating tides from the lower atmosphere. This indicates the existence of an unexpectedly strong, in situ forcing mechanism for semidiurnal oscillations in the high-latitude thermosphere. It is shown that the actual transition of tides in the altitude region between 90 and 150 km is more complex than described so far.